2003
DOI: 10.1111/j.1360-0443.2004.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Shape of the relapse curve and long‐term abstinence among untreated smokers

Abstract: More reports of relapse curves of self-quitters are needed. Smoking cessation interventions should focus on the first week of abstinence. Interventions that produce abstinence rates of 5-10% may be effective. Cessation studies should report relapse curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
883
3
38

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,228 publications
(962 citation statements)
references
References 48 publications
(54 reference statements)
38
883
3
38
Order By: Relevance
“…These high rates of relapse early on after an attempt in the current study are similar to that observed with other drug dependencies (Hughes et al, 2004) and suggest cannabis may be as dependence producing as other drugs. As importantly, such early relapse also suggests treatment programs need to schedule sessions very early on in any attempt to maintain marijuana abstinence.…”
Section: Success Of Abstinence and Reduction Attemptssupporting
confidence: 87%
“…These high rates of relapse early on after an attempt in the current study are similar to that observed with other drug dependencies (Hughes et al, 2004) and suggest cannabis may be as dependence producing as other drugs. As importantly, such early relapse also suggests treatment programs need to schedule sessions very early on in any attempt to maintain marijuana abstinence.…”
Section: Success Of Abstinence and Reduction Attemptssupporting
confidence: 87%
“…Despite several FDA approved treatments, the majority of smokers who attempt to quit will ultimately relapse and return to regular smoking behavior within the first year following a quit attempt (Hughes et al, 2004;Wileyto et al, 2004;Jorenby et al, 2006). Numerous risk factors for relapse have been identified (e.g., see Garvey et al, 1992;Doherty et al, 1995;Shiffman et al, 1996b;Ockene et al, 2000;Piasecki et al, 2000;Piasecki et al, 2003), and developing treatments to effectively target these many factors remain a high research priority.…”
Section: Introductionmentioning
confidence: 99%
“…First, it is possible that the benefits of medications decline, even in the context of RCTs. Many smokers who quit relapse 14, 15, 16, 17, leading to declines in quit rates over time 18, 19, 20, 21. This is well illustrated by a recent study ( n  = 1086), which found initial quit rates of at least 24 hours’ duration to be 70–80%, with declines over time to approximately 20% for varenicline, nicotine patch and combination nicotine groups by 1 year 22.…”
Section: Introductionmentioning
confidence: 85%